Perlakuan Dan Penanganan Yang Tepat Menurunkan Demam Anak Dengan Teknik Kompres Blok Di Pembuluh Darah Superfisial Dengan Teknik Seka Yang Menggunakan Air Hangat (Tepid Water Sponge) - Anurogo, Dito; Rahim, Abdul; Latif, Sarifudin Andi; Mudrika, Mudrika (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Compress is one of the alternatives used to maintain body temperature by using fluids or tools that can cause a warm reaction in the body area. One type of compress that can be used to lower body temperature in children with fever is tepid sponge. The purpose of Community Service is for proper handling in lowering children's fever with compress techniques. The implementation method in Community Service activities is health education about proper handling to lower children's fever with block compress techniques in superficial blood vessels and with wiping techniques in implementation using warm water in children. The results of community service obtained an increase in parental knowledge very well about proper handling to lower children's fever in meeting the need for comfort and maintaining normal temperature. The conclusion is that Typhoid fever is an acute infectious disease that usually affects the digestive tract with symptoms of fever for more than one week, digestive disorders, and impaired consciousness, Fever is rhythmic, usually decreases in the morning, and increases in the afternoon and evening. Clinical manifestations of typhoid fever in children are not typical and vary widely, but usually the typhoid triad is found, namely fever for more than 5 days, disorders of the gastrointestinal tract and can be accompanied or without disturbances of consciousness, and relative bradycardia.